Blue-Shifted Green Fluorescent Protein Homologues Are Brighter than Enhanced Green Fluorescent Protein under Two-Photon Excitation - Molina, Rosana S. (J Phys Chem Lett, 2017)
[Image: see text] Fluorescent proteins (FPs) are indispensable markers for two-photon imaging of live tissue, especially in the brains of small model organisms. The quantity of physiologically relevant data collected, however, is limited by heat-induced damage of the tissue due to the high intensities of the excitation laser. We seek to minimize this damage by developing FPs with improved brightness. Among FPs with the same chromophore structure, the spectral properties can vary widely due to differences in the local protein environment. Using a physical model that describes the spectra of FPs containing the anionic green FP (GFP) chromophore, we predict that those that are blue-shifted in one-photon absorption will have stronger peak two-photon absorption cross sections. Following this prediction, we present 12 blue-shifted GFP homologues and demonstrate that they are up to 2.5 times brighter than the commonly used enhanced GFP (EGFP).